2001
DOI: 10.1111/j.1525-1497.2001.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Problem drinking and medication adherence among persons with HIV infection

Abstract: OBJECTIVE:To examine the relation between problem drinking and medication adherence among persons with HIV infection. DESIGN:Cross-sectional survey.SETTING/PARTICIPANTS: Two hundred twelve persons with HIV infection who visited 2 outpatient clinics between December 1997 and February 1998. MEASUREMENTS AND MAIN RESULTS:Nineteen percent of subjects reported problem drinking during the previous month, 14% missed at least 1 dose of medication within the previous 24 hours, and 30% did not take their medications as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(97 citation statements)
references
References 26 publications
3
90
3
1
Order By: Relevance
“…Sixty percent of the members of this group were diagnosed with a current substance use disorder (alcohol or illicit drug), compared to rates of between 17 and 23% in the remaining groups. This finding is consistent with that of other researchers, who have found alcohol and drug use to be associated with poor adherence (Cook et al, 2001;Golin et al, 2002). Age also appeared to be a significant factor.…”
Section: Discussionsupporting
confidence: 94%
“…Sixty percent of the members of this group were diagnosed with a current substance use disorder (alcohol or illicit drug), compared to rates of between 17 and 23% in the remaining groups. This finding is consistent with that of other researchers, who have found alcohol and drug use to be associated with poor adherence (Cook et al, 2001;Golin et al, 2002). Age also appeared to be a significant factor.…”
Section: Discussionsupporting
confidence: 94%
“…Rather, the alcohol-risky sex association at the global-level for PLWHA appears to be bifurcated based on abstinence from alcohol versus the consumption of alcohol at any level. Although this finding is somewhat contrary to data from Fisher et al [19], unlike Fisher et al's meta-analysis, the present study focused solely on PLWHA, who have been shown to engage in higher levels of alcohol consumption and problematic drinking than non- infected individuals [5,6]. With this increased incidence of heavy alcohol consumption, a relatively larger proportion of PLWHA who consume alcohol may be classified as ''problematic drinkers,'' and this may therefore have led to a situation in the present meta-analysis in which there would have been considerable overlap between those in the ''any drinking'' category and those in the ''problematic drinking'' category.…”
Section: Discussioncontrasting
confidence: 67%
“…Some reports have even shown rates of unprotected sex among PLWHA to be as high as 84% [4]. Given the level of unprotected sex demonstrated by PLWHA, and recognizing that alcohol has not only been frequently implicated as a risk factor for unprotected sex, but also that heavy alcohol consumption tends to be more prevalent among PLWHA than among the general population [5,6], the present investigation sought to statistically assess the association between alcohol consumption and unprotected sex in PLWHA populations through a meta-analysis.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Alcohol consumption may interfere with the receipt of (Pence et al 2008) or adherence to (Cook et al 2001;Holmes et al 2007;Lazo et al 2007) HIV medications. It may also accelerate disease progression (Samet et al 2007), decrease survival (Braithwaite et al 2007), increase the damaging effect of HIV on cerebral frontal cortex function (Fein et al 1995), increase the risk of developing peripheral neuropathy (Max and Sherer 2000;Moyle and Sadler 1998), and impair immune functioning (Chen et al 1998).…”
Section: Introductionmentioning
confidence: 98%